Best practices and new norms in alternative dispute resolution - Ahmad, Muhamad Hassan (2021)
The recent technological advances, especially related to information technology (IT), to be even more specific Artificial Intelligence (AI), trigger the emergence of the Fourth Industry Revolution (IR4.0) which is very dynamic and progressive to the extent most of the major industries in the world have no option left but to transform the industry accordingly in order to survive in the IR4.0 era. Therefore, even well before the pandemic, we witness disruption in various industries. In this regard, the former Chief Justice of Malaysia, Tan Sri Richard Malanjum, mooted that: “[T]he legal profession must embrace technology. There is no option. It is coming soon to the legal profession. Adapt or be dropped”. Thus, the ADR, as a dispute resolution industry, is no exception and it has to go through transformation in the IR 4.0 era regardless of the occurrence of the COVID-19 pandemic.